Manifestações de utopia na narrativa de José Saramago - Feitosa, Fabiana Curto (2015)
This research proposes a reflection about the manifestation of utopia in the fictional work of the Portuguese writer José Saramago. The literary production of the writer shows up, compared to a contemporary reality that dehumanizes, something professedly engaged. Though he does not make pamphlet literature, Saramago demonstrates to stand out by the indicators elements of utopia as a social phenomenon. Therefore, this research aims to analyze the manifestations and (re)configurations of the utopian thoughts in the work of Saramago, seeking to collect elements that allows to define how his aesthetic and ethical project builds an structured utopia in the perspective of a left-wing writer, approaching the concrete utopia elaborated by the Marxist philosopher Ernest Bloch. Also, it dialogues, in that sense, with the conception -be left? created by Gilles Deleuze. Resuming some deleuzian approaches such as the question of perception and the becoming-minority, this study is dedicated to the literature of Saramago, in order to point out some features that assists in the process of identifying the type of engagement and politicization proposed in his works; as well in an attempt to investigate how the utopian elements presents themselves inserted in his works, while motto that awakes the critical consciousness, in a literary speech that reshapes the importance of concrete utopia as hope, praxis and resistance. Among the literary corpus studied, stands out Levantando do Chão, O conto da Ilha Perdida, Jangada de Pedra, Memorial do Convento and Ensaio sobre a cegueira.